Leucoencefalomalácia em equídeos da região Leste de Mato Grosso - Pereira dos Santos, Carlos Eduardo; Medeiros de Souto, Francisco Simiao; Santurio, Janio Morais; Marques, Luiz Carlos [UNESP] (Univ Fed Rio Grande do Sul, 2013)
Background: Fumonisins produced by Fusarium verticillioides are among the most important medical mycotoxins known. The intake of concentrate based on corn and corn by-products contaminated with fumonisins can cause severe poisoning in horses. The injuries are observed mainly in the white matter of the brain, and the disease is known as Equine Leukoencephalomalacia (ELEM). This study aims to describe and discuss the epidemiological, clinical and diagnostic aspects of an outbreak of ELEM occurred in three farms in the municipalities of Canarana and Agua Boa, in the eastern region of Mato Grosso, Brazil.Materials, Methods & Results: The outbreak occurred between May and August 2010. The disease affected six horses and four mules of different ages and sex. Clinical examination was only possible in animals with chronic evolution of the disease. All the affected animals showed neurological clinical signs such as ataxia and recumbency, which progressed to death or sudden death. Histopathological analysis showed foci of necrosis that predominantly affected the white matter, and the presence of gitter cells. Degenerative lesions were observed in the liver of the animals. Mortality rate ranged from 12.5 to 71%, and lethality reached 100%. The cases were preceded by sudden drops in the weather temperature. Fumonisins levels of 6.6 ppm were detected in the feed of the animals.Discussion: The presumptive diagnosis of leukoencephalomalacia was consistent and based on clinical and epidemiological studies. However, the definitive diagnosis was based upon the histological features of the brain including the presence of extensive areas of malacia. Moreover, the animals were being fed with corn or corn by-products contaminated with fumonisins levels considered to be toxic to equids. The mortality and lethality rates are in agreement with outbreaks described in previous studies. The animals showed neurological signs as the predominant clinical manifestation, with gait ataxia followed by recumbency, prostration and death between 24 h and 29 days. Similarly to other reports, the disease was more frequent in adult animals, which succumbed in 24-48 h. Conversely, the evolution of the disease in young animals was of 10 to 29 days. Sudden death was more prevalent in the mules. Previous studies have shown a predominance of cerebral and brainstem lesions in horses, whereas in mules the clinical signs are related to brainstem lesions. Corn and corn by-products are commonly used as energy supplementation to horses in the southern of Mato Grosso state, but outbreaks of the disease are uncommon. This may be influenced by the prevalence of hot climate conditions, which does not favor the production of toxin by the fungus. The atypical low weather temperatures (9-11 degrees C) observed prior to the outbreak could have contributed to the mycotoxin production by F. verticillioides, which requires temperatures between 8-12 degrees C to produce toxins. However, the disease in the region may be underestimated, considering that the practice of necropsies is not common among field technicians, mainly in the occurrence of sporadic deaths among horses intended for work. Preventive measures include avoiding the use of corn and corn by-products for horses after periods of sudden drops in temperature in the region. Furthermore, clinical and epidemiological surveys and post-mortem and histopathological analyses are undoubtedly important for appropriate differential diagnosis, especially in equids with neurological signs.
Leukoencephalomacia in Equidae of the Eastern Region of Mato Grosso, Brazil
Keywords: mycotoxins; equine leukoencephalomalacia; epidemiology; fumonisins; Horse; mules